복합운동프로그램이 중년 여성의 신체구성, 건강관련체력 및 대사증후군 위험인자에 미치는 영향 - 오수일; 황예선; 유민주 (The Asian journal of kinesiology, 2013)
[서론] 본 연구는 복합운동 프로그램이 비만하면서 고혈압과 당뇨의 대사증후군 위험인자를 동반한 중년 여성의 신체구성, 건강관련체력, 대사증후군에 어떠한 영향을 미치는지 알아보았다. [방법] 연구대상자는 28명의 비만 중년여성 중 비만하면서 고혈압을 갖고 있는 고혈압 집단과(n=15. SBP≥140mmHg) 비만하면서 당뇨를 갖고 있는 당뇨 집단(n=13, glucose≥120mg/㎗)으로 각각 구분하였다. 운동 프로그램은 10주간, 주 3회, 80분 간(준비운동 10분, 본운동 60분, 정리운동 10분)으로 하였으며, 유산소운동(트레드밀 걷기+고정식 바이크 싸이클링)과 저항운동(free weight 이용)을 병행한 복합운동을 실시하였다. [결과] 신체구성 결과, 두 집단 모두 제지방량을 제외한 체중, 체지방량, BMI, 체지방률에서 유의하게 감소하였다. 건강관련체력에서는 고혈압 집단이 근력, 근지구력, 유연성에서, 당뇨 집단이 근지구력, 유연성, 심폐지구력에서 유의하게 증가하였다. 대사증후군 위험인자에서는 고혈압 집단이 수축기혈압, WHR에서 유의하게 감소하였으며, 당뇨 집단은 glucose에서 유의한 감소와 HDL-C에서 유의한 증가가 나타났다. 이원반복변량분석 결과 수축기 혈압과 글루코스에서 유의한 상호작용 효과가 있는 것으로 나타났다. [결론] 본 연구의 결과를 보았을 때 비만을 동반한 고혈압 및 당뇨를 가진 중년여성에게 있어 복합운동의 적용이 신체구성, 건강관련체력 및 대사증후군 위험인자에 긍정적인 측면의 결과를 미치는 것으로 나타났다. 특히 10주간의 복합운동 후 고혈압집단에서 수축기 혈압이 유의하게 감소하였고 당뇨집단에서 글루코스가 유의하게 감소하였다. 본 운동 프로그램을 장기간 적용한다면, 대사증후군과 관련된 질환을 예방할 수 있는 프로그램으로 활용할 수 있을 것으로 생각된다. [INTRODUCTION] The purpose of the study was to investigate the effects of combined exercise program on the body composition, health-related physical fitness, and metabolic syndrome risk factor in middle-aged women(n=28) who has hypertension or diabetes with obesity. [METHOD] The combined exercise program performed 10 weeks with 80 minutes per day and 3days per week and aerobic exercise with resistance exericse. The participants was divided into two groups; hypertension group(n=15, systolic blood pressure≥140mmHg) and diabetes group(n=13, glucose≥120mg/dl). [RESULT] The change of body composition after 10 weeks, body weight, fat mass, BMI, %fat were significantly decreased two groups all. The Health-related physical fitness of hypertension group, muscle strength, muscle endurance, flexibility were significantly increased and diabetes group, muscle endurance, flexibility, cardiorespiratory endurance were significantly increased. In the metabolic syndrome risk factor, hypertension group were significantly decreased on blood pressure, WHR. diabetes group were significantly decreased on glucose, but HDL-C was significantly increased after 10 weeks after and there were significantly interaction on systolic blood pressure and glucose. [CONCLUSION] These results showed that combined exercise program have beneficial effect that positive change of body composition health-related physical fitness and metabolic syndrome risk factor in middle-aged women who has hypertension or diabetes with obesity. Especially systolic blood pressure in hypertension group and glucose in diabetes group have decreased by combined exercise program. So if this program applies for a long time, we think it can use effective to prevent related metabolic syndrome risk factor disease KCI Citation Count: 16